PERAN TATA KELOLA DAN TANGGUNG JAWAB SOSIAL DALAM MENINGKATKAN NILAI PERUSAHAAN DENGAN UKURAN PERUSAHAAN SEBAGAI MEDIASI - Rahelita Suganda; Ickhsanto wahyudi (Jurnal Ekonomi Bisnis dan Akuntansi, 2023)
The purpose of this study is to determine the determinants of corporate value such as corporate governance and social responsibility mediated by company size. This study utilizes information taken from the financial reports of the coal subsector listed on the IDX using a purposive sampling test method that meets the exploration steps. The research period was taken for 3 years with the amount of information used, namely 57 data from 21 entities in the coal subsector. The research method uses Partial Least Square (PLS) with secondary data types. The results of the study show that corporate governance is able to positively influence firm value. But the existence of company size can’t mediate the correlation between firm value and corporate governance. Whereas, corporate social responsibility is not able to influence company value but the existence of company size as a mediation is able to positively influence the correlation between corporate social responsibility and company value.